Some Phonological Processes in Dibaji - Shahram Naghshbandi; Havva Hajeidi (مطالعات زبانی و بلاغی)
This research aims at the description and analysis of some aspects of the phonology of Dibaji variety from the perspective of Standard Generative Phonology. Dibaji is classified as one of the Caspian varieties of Western Iranian Languages family .The Dibaji dialect is spoken in the city of Dibaj, located in the North of Damghan city in Semnan province. The required data were collected through completing questionnaires and interviewing with five native speakers (mainly older than 45 illiterate and less educated). One of the authors of the present research is also a native speaker of Dibaji. This research is descriptive-analytical.The data are transcribed in International Phonetic Alphabet (IPA). The phonological processes studied in the research are assimilation, dissimilation, deletion, insertion, lenition, and metathesis. The processes are selected based on their frequent occurrence in the corpus and their remarkable differences with the existing phonological processes in Standard Farsi. After describing each phonological process, the related phonological rule was formulated to account for the existing regularity. If there is any rule interaction with other existing rules in this research, it is introduced and discussed accordingly.